Plant Community and Diversity Patterns within the Forested Landscape of North-eastern U. P. - Pande, S. K.; Shukla, R. P. (Indian Forester, 2005)
A Synthesis of observations was made for phytosociological characterization of the regional forested landscape of North-eastern Uttar Pradesh which is a mosaic of major and minor plantation forests and interspersed pathes of mixed forests. The latter showed greater species richness and number of trees, shrubs and Hanas than the associated communities of plantation forests of Sal and Eugenia. The Shannon’s index (Î±-diversity) was however, maximum for Sal stands followed by mixed forests and Sal-Teak combination but the index was much lower for Trewia and Terminalia stands. Î³-diversity for the regional forested landscape was 4.035. The species-area curves suggesed that the increase in the number of species was more regular in mixed forest and in some Sal stands as compared to other stands. The general form of the dominance-diversity curve for the forested landscape was quite normal but that for trees (>30 cm gbh) showed a steep decline. Rare occurrences of many species may be due to the loss of naural associations of several genera in presence of recurrcnt disturbance. Nevcrtheless, the fairly high species richness and plant diversity suggest that the regional forested landscape is still able to provide the much required gene pool for the conservation of species and ecosysems of the region.